DEVELOPMENT AND EVALUATION OF IN-SITU GELLING OTIC FORMULATIONS OF METRONIDAZOLE USING POLOXAMER - D. L. MALI; K. R. KATTEKAR; M. J. DESHPANDE; S. V. SHIROLKAR (The Bioscan, 2011)
The purpose of this study was to develop a sustained release in situ gel formulations for the treatment of chronic suppurative otitis media with the aim to increase drug concentration in the middle ear fluid. Poloxamer 407 was used as in situ gelling agent and Metronidazole was used as an active ingredient. In an attempt to reduce the concentration of Poloxamer 407 without compromising the in situ gelling capabilities, various viscosity increasing agents were added to Poloxamer 407 solution containing 0.75% Metronidazole. The formulations were evaluated for appearance / clarity, sol-gel transition temperature, gelling time, pH, spreadability, rheological characteristic and in vitro diffusion through synthetic as well as biological membrane. The viscosity of formulation increased as the concentration of Poloxamer 407 increased. The viscosity of formulation increased as the concentration of viscosity increasing agent was increased in the formulation containing constant amount of Poloxamer 407.